An optimal load shedding scheme based on the analytical heirarchy approach: a case study of the Selangor Electrical System - Tasuki, Norazleen (2014)
Most people depend on electrical energy in every aspect of their life. All sectors in Malaysia really need electrical energy to remain stable and consistent. As consumers, the public are want to have constant distributed of electricity energy without any disturbances. For example, food industries will be experiencing large financial lost if there are disturbances in electrical supplies even for only one day. If the total electrical load power demand greatly exceeds than the power supplied and no decision-making in removing a certain load, it will affect to the power system. Certain loads will be have to remove and needs some decision-making process in order to choose the best load(s) to be cut off. The load shedding process automatically detects overload conditions, then shed enough load to relieve the overloaded equipment before there is loss of generation, line tripping, equipment damage, or a chaotic random shutdown of the system. In this paper, an analysis is made to find the best method to be applied in load shedding. Analytical Hierarchy Process (AHP) and Technique for Order Preferences by Similarity to Ideal Solution (TOPSIS) is two methods most widely applied techniques MADM/MCDM problem. By using the AHP and TOPSIS methods, the priority of the load can be determined. This paper is focusing on the analysis of alternative methods in choosing the load priority of load shedding scheme in Selangor Electrical system. By using the AHP and TOPSIS methods, both have its own advantages in approach to determine the sequences of load to be shed.